2015
DOI: 10.56093/ijas.v85i7.50091
|View full text |Cite
|
Sign up to set email alerts
|

Paclobutrazol use in perennial fruit crops and its residual effects: A review

Abstract: Paclobutrazol (PBZ), a triazole derivative, has been effectively used to induce and manipulate flowering, fruiting and tree vigour in several perennial fruit crops. However its use in mango is quite common. Soil application of paclobutrazol has been efficacious in promoting flowering and increasing yield in many fruit crops. However, there are some conflicting reports on its impact on fruit quality parameters. Besides reducing gibberellins level, PBZ increases cytokinin contents, root activity and C: N ratio, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 69 publications
0
1
0
Order By: Relevance
“…The reduction in NPQ by PBZ suggests that the PBZ-treated sage plants were the least stressed as they had less excess energy to release. Different studies have reported that PBZ-treated plants show an increased resistance to abiotic and biotic stresses [1]; it has been related to the influence of PBZ on hormonal balance and gene expression [46]. Triazoles such as PBZ have been documented to impact the isoprenoid pathway and modify specific hormone levels.…”
Section: Controlmentioning
confidence: 99%
“…The reduction in NPQ by PBZ suggests that the PBZ-treated sage plants were the least stressed as they had less excess energy to release. Different studies have reported that PBZ-treated plants show an increased resistance to abiotic and biotic stresses [1]; it has been related to the influence of PBZ on hormonal balance and gene expression [46]. Triazoles such as PBZ have been documented to impact the isoprenoid pathway and modify specific hormone levels.…”
Section: Controlmentioning
confidence: 99%
“…Dentre estes reguladores, o paclobutrazol (PBZ) é um dos mais utilizados para reduzir o tempo entre a fase juvenil e reprodutiva (Taiz e Zeiger, 2017). O PBZ é transportado acroptamente via xilema, embora já tenha sido observado no fl oema (Kishore et al, 2015) e tem sido utilizado com sucesso para regulação do fl orescimento em plantas perenes (Nartvaranant et al, 2000). O PBZ é um membro do grupo dos reguladores de crescimento triazóis, que inibe a biossíntese de giberelinas (Desta e Amare, 2021).…”
Section: Atuação Do Paclobutrazolunclassified
“…The issue of partitioning of assimilates among the various plant organs could be solved to some extent with the help of plant growth regulators. Kishore et al, (2015) reported the residual effect of the Paclobutrazol, such that it is considered moderately hazardous for human beings with r e m o t e c h a n c e o f b e i n g g e n o t o x i c a n d c a r c i n o g e n i c . T h e o p t i m i z e d u s e o f t h e paclobutrazol offers maximum benefit with least undesirable effect.…”
mentioning
confidence: 99%